VHPKQHR Peptide Modified Ultrasmall Paramagnetic Iron Oxide Nanoparticles Targeting Rheumatoid Arthritis for T1-Weighted Magnetic Resonance Imaging - Zhang, Chunyu; Huang, Wentao; Huang, Chen; Zhou, Chengqian; Tang, Yukuan; Wei, Wei; Li, Yongsheng; Tang, Yukuan; Luo, Yu; Zhou, Quan; Chen, Wenli (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic resonance imaging (MRI) could be the ideal diagnostic modality for early rheumatoid arthritis (RA). Vascular cell adhesion molecule-1 (VCAM-1) is highly expressed in synovial locations in patients with RA, which could be a potential target protein for RA diagnosis. The peptide VHPKQHR (VHP) has a high affinity to VCAM-1. To make the contrast agent to target RA at an early stage, we used VHP and ultrasmall paramagnetic iron oxide (USPIO) to synthesize UVHP (U stands for USPIO) through a chemical reaction with 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-Hydroxysuccinimide (NHS). The size of UVHP was 6.7 nm, the potential was -27.7 mV, and the r2/r1 value was 1.73. Cytotoxicity assay exhibited that the cell survival rate was higher than 80% at even high concentrations of UVHP (Fe concentration 200 μg/mL), which showed the UVHP are low toxicity. Compared to no TNF-𝛼 stimulated, VCAM-1 expression was increased nearly 3-fold when mouse aortic endothelial cells (MAECs) were stimulated with 50 ng/mL TNF-𝛼; cellular Fe uptake were increased very significantly with increasing UVHP concentration under TNF-𝛼 treatment, cellular Fe content was 17 times higher under UVHP with Fe concentration 200 μg/mL treating MAECs. These results indicated UVHP can target overexpression of VCAM-1 at the cellular level. RA mice models were constructed with adjuvant-induced arthritis (AIA). In vivo MRI and biodistribution results showed that the signal intensity of knee joints was increased significantly and Fe accumulation in RA model mice compared with normal wild-type mice after injecting UVHP 24 h. These results suggested that we have synthesized a simple, low-cost, and less toxic contrast agent UVHP, which targeted VCAM-1 for early-stage RA diagnosis and generates high contrast in T1-weighted MRI.